Pattern development - Ingham, Rosemary (Leucadia Insight Media [distributor], 1989, 2008.)
Costume designer Rosemary Ingham demonstrates her simple, straightforward way of creating patterns from measuring the actor to fitting the design mock-up.
Part 1. Taking Accurate Measurements -- Part 2.Analyzing the Desig -- Part 3. Developing the Pattern -- Part 4. Fitting for the Mockup.
DVD
Credits: Executive producer, Ron Ronson, Jr. ; director, Ken Kebow ; writer/author, Rosemary Ingham ; co-author, Liz Covey.
Rosemary Ingham.
Keywords: Costume design; Dressmaking -- Pattern design; Tailoring -- Pattern design